The Nature and Structure of Scientific Theories - Moulines, C. Ulises (Universidad Nacional de Quilmes, 2010)
Fil: Moulines, C. Ulises. University of Munich. Seminar für Philosophie, Logik und Wissenschaftstheorie; Alemania.